Al-`Urf sebagai Dalil Hukum Ekonomi dan Keuangan Syariah - Noorwahidah (Islamic Economics and Business Faculty of UIN Antasari, 2026)
Al-'urf, the customary practice prevailing in society, is one of the subsidiary legal proofs employed by usul al-fiqh scholars to establish rulings in Islamic economics and finance for cases not explicitly addressed by the primary texts. Although the literature on al-'urf as a source of Islamic economic law is abundant, most existing studies remain conceptual, relying on conventional illustrations such as bay' al-mu'atah or istisna' without examining the doctrine's application to contemporary digital sharia-economy products. This study analyzes the juristic standing of al-'urf as a legal proof and its application across five contemporary legal instruments: the DSN-MUI fatwas on the Sharia Card, Sharia Electronic Money, Sharia Peer-to-Peer Fintech Financing, and Dropshipping, together with the Ijtima Ulama Decision on cryptocurrency. The method employed is structured library research using content analysis of usul al-fiqh literature and fatwa consideranda. The findings show that the maxim al-'adah muhakkamah is explicitly invoked as a legal basis in DSN-MUI Fatwa No. 54/DSN-MUI/X/2006 on the Sharia Card, and implicitly underlies the acceptance of cashless transaction customs and order-based contracts in the remaining products, provided four conditions of valid ('urf sahih) custom are satisfied: it must embody genuine benefit (maslahah), be widely practiced, predate the case at hand, and not contradict the revealed texts. The study further corrects a recurring error in the secondary literature that attributes the report “ma ra'a al-muslimuna hasanan” to a marfu' hadith of the Prophet, whereas its properly authenticated status is a mawquf report traced to Ibn Mas'ud in the Musnad of Ahmad ibn Hanbal. The principal contribution of this study is an analytical framework mapping sahih and fasid 'urf onto contemporary digital economic instruments through the lens of maqasid al-shariah.